The Global Increase in Counterfeit Pesticides - Frederick M. Fishel (EDIS)
PI-174, an 8-page illustrated fact sheet by Frederick M. Fishel, describes the growing problem of illegal manufacture and trade of counterfeit pesticides, types of counterfeit and illegal pesticides, effects of illegal trade and counterfeit pesticides, challenges to fighting the problem, steps that need to be taken, and examples. Includes sources of additional information. Published by the UF Department of Agronomy, January 2009.